2021
DOI: 10.1212/nxi.0000000000000998
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Transglutaminase Expression Associates With Progression of Multiple Sclerosis

Abstract: ObjectiveThe clinical course of multiple sclerosis (MS) is variable and largely unpredictable pointing to an urgent need for markers to monitor disease activity and progression. Recent evidence revealed that tissue transglutaminase (TG2) is altered in patient-derived monocytes. We hypothesize that blood cell–derived TG2 messenger RNA (mRNA) can potentially be used as biomarker in patients with MS.MethodsIn peripheral blood mononuclear cells (PBMCs) from 151 healthy controls and 161 patients with MS, TG2 mRNA w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…TG2 is increased in MS patient-derived monocytes, affecting their adhesion and migration into the CNS [176]. In keeping with this, elevated TG2 mRNA levels have been reported in peripheral blood mononuclear cells in MS patients, a finding that correlated with disease progression [176,177], suggesting TG2 as both a biomarker and therapeutic target for MS.…”
Section: Tg2 In Other Neurodegenerative Disorderssupporting
confidence: 57%
See 1 more Smart Citation
“…TG2 is increased in MS patient-derived monocytes, affecting their adhesion and migration into the CNS [176]. In keeping with this, elevated TG2 mRNA levels have been reported in peripheral blood mononuclear cells in MS patients, a finding that correlated with disease progression [176,177], suggesting TG2 as both a biomarker and therapeutic target for MS.…”
Section: Tg2 In Other Neurodegenerative Disorderssupporting
confidence: 57%
“…Multiple sclerosis (MS) is a relapsing-remitting or primary progressive disease characterized by neuroinflammation, demyelination, and, eventually, axon loss and neurodegeneration in the CNS. Accumulating evidence from studies has identified the involvement of TG2 in postmortem MS brain samples and in the central nervous system of the animal model for experimental autoimmune encephalomyelitis (EAE), illustrating its role in the pathogenesis of MS [174][175][176][177][178]. For example, TG2 knock-out mice subjected to the EAE model exhibited decreased disease severity compared to wild-type littermates, and treatment with the TG2 inhibitor cysteamine in the EAE effector phase in wild-type mice showed benefits [179].…”
Section: Tg2 In Other Neurodegenerative Disordersmentioning
confidence: 99%
“…TG2 possesses a wide variety of activities, from acting as a GTPase and kinase to a transamidase and scaffolding protein with many substrates across various intracellular compartments, the cell surface, and within the extracellular space. These interactions are important for cell survival [ 27 , 28 ] and the phagocytic function of the macrophages in tissue repair [ 29 , 30 , 31 ], but can also contribute to increased inflammation [ 32 ] and cell-death [ 33 ] in neurodegenerative conditions [ 34 ], including Huntington disease (HD) [ 35 ], Alzheimer disease (AD) [ 36 ], Amyotrophic Lateral Sclerosis (ALS) [ 37 ], and Multiple Sclerosis (MS) [ 38 , 39 , 40 , 41 ]. Recently, our group and others identified TG2 dysregulation in cadaveric MS brain samples and in the CNS of rodents with EAE (experimental autoimmune encephalomyelitis) [ 38 ], highlighting its role in the pathogenesis of MS.…”
Section: Introductionmentioning
confidence: 99%
“…In EAE, TG2 is expressed in infiltrating monocytes [ 41 ], promoting their adhesion and tissue migration into the CNS [ 41 ]. Sestito et al [ 39 ] demonstrated that this elevated TG2 in the monocytes of MS patients correlated with the progression of the clinical course of disease in MS [ 39 , 42 ], suggesting that TG2 is an important therapeutic target to alter the disease course in MS. Extracellular TG2 also crosslinks with various extracellular matrix (ECM) molecules such as Fibronectin (FN) [ 43 ] and Heparin Sulfate Proteoglycan (HSPG) [ 44 ], which are known to mediate inflammation and promote tissue scarring, which is inhibitory to repair [ 45 ]. Selective deletion of TG2 in astrocytes has been demonstrated to perturb the production of the chondroitin sulfate proteoglycan (CSPG) NG2 after spinal cord injury (SCI) [ 46 ] and to improve neuronal survival when these TG2 depleted astrocytes are co-cultured with neurons in vitro following exposure to cytotoxic stimuli [ 47 ].…”
Section: Introductionmentioning
confidence: 99%